2018
DOI: 10.1080/15384101.2018.1542901
|View full text |Cite
|
Sign up to set email alerts
|

MiR-130a-5p prevents angiotensin II-induced podocyte apoptosis by modulating M-type phospholipase A2 receptor

Abstract: Podocyte apoptosis is considered as the important element that promotes the development and progress of membranous nephropathy (MN). Unfortunately, the underlying mechanism of podocytes apoptosis in MN remains elusive. We compared the renal expressions of miR-130a-5p and M-type phospholipase A2 receptor (PLA2R) between MN patients (n = 30) and 30 controls by qRT-PCR and western blot, respectively. The podocyte damage model in vitro was established by angiotensin II (Ang II, 100 nmol/L) exposure for 24 h. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Further analysis is required to explore the effect of miR-125b in renal diseases. miR-130a: Liang et al reported that miR-130a protected LPS-induced glomerular injury by Klotho upregulation [67]. They also indicated that miR-130a activated PI3K/AKT pathway and inhibited Wnt and NF-κB pathway [67].…”
Section: Versatile Msc-evs-derived Mirnas Modulate Renal Injury and Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis is required to explore the effect of miR-125b in renal diseases. miR-130a: Liang et al reported that miR-130a protected LPS-induced glomerular injury by Klotho upregulation [67]. They also indicated that miR-130a activated PI3K/AKT pathway and inhibited Wnt and NF-κB pathway [67].…”
Section: Versatile Msc-evs-derived Mirnas Modulate Renal Injury and Hmentioning
confidence: 99%
“…miR-130a: Liang et al reported that miR-130a protected LPS-induced glomerular injury by Klotho upregulation [67]. They also indicated that miR-130a activated PI3K/AKT pathway and inhibited Wnt and NF-κB pathway [67]. Liu et al reported that miR-130a-5p prevented angiotensin II-induced podocyte apoptosis by modulating phospholipase A2 receptor (PLA2R) [68].…”
Section: Versatile Msc-evs-derived Mirnas Modulate Renal Injury and Hmentioning
confidence: 99%
“…Rahbar et al analyzed the expression pattern of the glucocorticoid receptors α and β, and their epigenetic regulators, miR-24, miR-30a and miR-370 in peripheral blood mononuclear cells, and reported that the increase in miR-30a and miR-370 levels as well as the decrease in miR-24 levels were observed in MGN patients compared to FSGS patients, while no significant differences in glucocorticoid receptors α and β expressions were observed between MGN, FSGS and healthy controls, indicating that dysregulation levels of glucocorticoid receptors α and β were not attributed to steroid resistance [ 36 ]. Liu et al found that miR-130-5p potentially regulates PLA2R1 and, thus, investigated the correlation between miR-130-5p and MGN, and reported the decreased expression of miR-130-5p in kidneys of MGN patients [ 37 ]. They conducted animal experiments and demonstrated that the decrease in miR-130a-5p expression may increase PLA2R expression, thereby inducing podocyte apoptosis.…”
Section: Mirnas In Membranous Glomerulonephropathymentioning
confidence: 99%
“…A study has reported that miR‐130a‐5p prevents angiotensin II‐induced podocyte apoptosis by modulating M‐type Phospholipase A2 Receptor 21 . Similarly, we established the podocyte injury model by AngII in vitro.…”
Section: Discussionmentioning
confidence: 90%